A pilot investigation of the efficacy and safety of magnesium chloride and ethanol as anesthetics in Loligo vulgaris embryos - Sprecher, Marta; Sprecher, Simon G.; Spadavecchia, Claudia (Frontiers in Physiology, 2022)
The inclusion of Cephalopods in the legislation related to the use of animals for experimental purposes has been based on the precautionary principle that these animals have the capacity to experience pain, suffering, distress, and lasting harm. Recent studies expanded this view and supported it. Handling of cephalopod mollusks in research is challenging and whenever more invasive procedures are required, sedation and/or anaesthesia become necessary. Therefore, finding adequate, safe, and effective anaesthetics appears mandatory. Several substances have been considered in sedating cephalopods, in some instances applying those utilized for fish. However, species-specific variability requires more detailed studies. Despite long-lasting experience linked to classic studies on squid giant axons, evidences of action on putative anaesthetic substances is scarce for Loligo vulgaris and particularly for their embryos. Aim of the current study was to evaluate effects and adverse responses elicited by immersion of squid embryos in anaesthetic solutions and examine whether these forms can display similar reaction to anaesthetic as adults. Different concentrations of ethanol (EtOH; 2, 2.5, 3%) and magnesium chloride (MgCl2; 1, 1.5, 1.8%) were tested adopting a set of indicators aimed to explore physiological responses of squid embryos. Forty-two embryos of the common squid Loligo vulgaris were assigned to three conditions (EtOH, MgCl2 and controls) and video-recorded for 15 minutes (5 min before, 5 min during and 5 min after immersion in the anaesthetic solutions). In each group heart rate, respiratory rate, buoyancy, chromatophores activity and tentacles/arms response were assessed to evaluate embryos vitality and responsiveness to stimulation. Both substances provoked a decrease in heart and respiratory rate and inhibited buoyancy, chromatophores and tentacles/arms responses. EtOH had a faster onset of action and faster recovery than MgCl2, being potentially more adequate as an anaesthetic for shorter procedures. Even though MgCl2 caused a longer muscle relaxation, reversibility was not confirmed for the 1.8% concentration, however lower concentration triggered similar results as the ones obtained with the highest EtOH concentrations. We show that late developmental stages of Loligo vulgaris embryos could represent a good model to evaluate anaesthetics for cephalopods since they can display similar anaesthetic reactions as adult animals.